2021
DOI: 10.3390/jfb12040059
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Antimicrobial Nanofibers: Design Criteria and Recent Advances

Abstract: The rise of antibiotic resistance has become a major threat to human health and it is spreading globally. It can cause common infectious diseases to be difficult to treat and leads to higher medical costs and increased mortality. Hence, multifunctional polymeric nanofibers with distinctive structures and unique physiochemical properties have emerged as a neo-tool to target biofilm and overcome deadly bacterial infections. This review emphasizes electrospun nanofibers’ design criteria and properties that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 233 publications
0
44
0
Order By: Relevance
“…In comparison with other epithelial components (i.e., gelatin, elastin, collagen, and sericin), extracted-keratin is a biodegradable and water-soluble protein with a cytocompatibility and non-immunogenic response due to their peculiar cell-binding motifs (i.e., arginine-glycine-aspartic acid) [57,58]. Recent studies confirmed the advantages of using keratin electrospun-NFs for wound healing applications because of their high porosity and capacity to absorb exudates [59]. Different content of KS and thermal treatments enables modifying the wettability, the microscopic properties of NFs, and the secondary structure content of KS, which confer different properties in terms of flexibility and chain elasticity, able to slightly influence cell response in vitro, in agreement with previous studies [60].…”
Section: Discussionmentioning
confidence: 95%
“…In comparison with other epithelial components (i.e., gelatin, elastin, collagen, and sericin), extracted-keratin is a biodegradable and water-soluble protein with a cytocompatibility and non-immunogenic response due to their peculiar cell-binding motifs (i.e., arginine-glycine-aspartic acid) [57,58]. Recent studies confirmed the advantages of using keratin electrospun-NFs for wound healing applications because of their high porosity and capacity to absorb exudates [59]. Different content of KS and thermal treatments enables modifying the wettability, the microscopic properties of NFs, and the secondary structure content of KS, which confer different properties in terms of flexibility and chain elasticity, able to slightly influence cell response in vitro, in agreement with previous studies [60].…”
Section: Discussionmentioning
confidence: 95%
“…Some nanomaterials are also able to mix with the bacterial cell wall to release their antimicrobial material into the cytoplasm [ 46 , 53 ]. Antimicrobial nanofibers can also pass through the bacteria pores due to their very small diameter and can then disrupt the bacteria’s different functions [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surface charge and surface wettability and can be considerably enhanced by incorporation of antimicrobial agents such as metal/metal oxide NPs, carbon nanomaterials, AMPs or natural plant or herbal extracts. The functionalization of electrospun nanofibers with antimicrobial agents can be utilized to fight bacterial infections and resistance and is a promising strategy to combat bacterial infection and resistance [ 188 , 189 , 190 , 191 ]. The ethylcellulose/gum tragacanth (85:15) electrospun nanofibrous mats with incorporated honey (5–20 wt%) were evaluated as an effective wound covering biomaterials characterized with antibacterial properties, improved antioxidant activity, good mechanical properties and degradation ability features, and showed proper cell growth, attachment, and proliferation against NIH-3 T3 fibroblast cells [ 192 ].…”
Section: Applied Nanomaterialsmentioning
confidence: 99%